Oral administration of resveratrol reduces oxidative stress generated in the hippocampus of Wistar rats in response to consumption of ethanol - Navarro-Cruz, Addí Rhode; Juárez-Serrano, Daniel; Cesar-Arteaga, Ivan; Kammar-García, Ashuin; Guevara-Díaz, Jorge Alberto; Vera-López, Obdulia; Lazcano-Hernández, Martin; Pérez-Xochipa, Ivonne; Segura-Badilla, Orietta (Frontiers in Behavioral Neuroscience, 2024)
Chronic ethanol intake has been found to favor hippocampal deterioration and alter neuronal morphological maturation; resveratrol has been suggested as an antioxidant that may counteract these effects. The objective of this work was to analyze the effect of resveratrol on oxidative stress markers, endogenous antioxidant system in the hippocampus and in behavior of male Wistar rats administered different concentration of ethanol. The animals, at 3 months old, were randomly distributed eleven study groups (n= 6/group), orally administered (five days on, two days off) with water (control), ethanol (10, 20, 30, 40 or 50%), or ethanol (10, 20, 30, 40 or 50%) plus resveratrol (10 mg/Kg/day) for two months. Subsequently, the production of nitrites, malondialdehyde and 4-hydroxy-alkenal (HNE) as well as the enzymatic activity of Catalase and Superoxide dismutase (SOD) were quantified. Levels of nitric oxide and lipid peroxidation products were significantly increased in each ethanol concentration and was statistically different compared to the control group, however, resveratrol significantly reduced oxidative stress caused in high ethanol concentration. The SOD and CAT did not present significant changes with respect to the controls in any of the study groups. In the different concentrations of ethanol used, GR increases significantly in the groups administered with resveratrol but not GPx. Resveratrol was shown to maintain results similar to the control at most ethanol concentrations. Our results suggest that resveratrol prevents oxidative stress induced by ethanol in the hippocampus by decreasing cellular lipid peroxidation, but not the activation of catalase or SOD enzymes, but also allows glutathione to be kept active and in adequate concentrations in its reduced form and avoid alterations in the locomotor system.